Retno Sri Handini - Retno Sri Handini (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2019)
Stakeholder interests have been taken as the important aspect and become the elements of the corporate environment. This study aimed at understanding the enabling factors of sustainability activity including internal aspects such as the role of vision and mission, top management, and value chain. The implementation of sustainability was also analyzed by the stakeholder perspective that consists of the orientation toward consumer, employee, supplier, government, environment, community, and government. This study also analyzed the types of sustainability activity of each company. The data were taken by having an interview with three big companies in Indonesia. They were from industry of mining, food and beverage and heavy equipment. The result showed that the companies implemented sustainability activities by focusing on stakeholder perspectives including consumer, employee, supplier, government, environment, community, government.